ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN PADA PT. PERKEBUNAN NUSANTARA III (PERSERO) PABRIK KELAPA SAWIT (PKS) RAMBUTAN - Wesly Simanjuntak (LP2MTBM MAKARIOZ, 2019)
The purpose of this study was to determine and analyze the sales accounting information system at PT. Plantation Nusantara III (Persero) Palm Oil Mill (PKS) Rambutan. The type of data used in this study is secondary data. The data is sourced from PT. Perkebunan Nusantara III (Persero) Palm Oil Mill (PKS) Rambutan in the form of the history of the establishment of the company, picture of the organizational structure, sales data and sales accounting information system. The data analysis technique used is descriptive method and comparative method. Based on the discussion of the results of the study, it is known that the parts involved in the sale of PT. Perkebunan Nusantara III (Persero) Rambutan Palm Oil Mill (PKS) is a buyer, marketing department, logistics department, finance department and accounting department. The functions related to the sales accounting information system are marketing functions, warehouse functions, shipping functions and accounting functions. Sales of PT. Perkebunan Nusantara III (Persero) Palm Oil Mill (PKS) Rambutan in 2015 and 2017 has decreased, while in 2014 and 2016 has increased. Sales accounting information system at PT. Perkebunan Nusantara III (Persero) Oil Palm Plant (PKS) Rambutan has not been implemented effectively.